Pengawasan Mutu Olahan Kacang Mete pada PT East Indo Fair Trading, Kabupaten Karangasem, Provinsi Bali - A. A. A. ISTRI PRIYATNA WULANDARI; RATNA KOMALA DEWI; KETUT RANTAU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Cashew Nut Product Quality Control In PT East Indo Fair Trading, Karangasem Regency, Bali ProvincePT East Indo Fair Trading is one of cashew nut manufacturing company in Bali. Company has been applied management quality in accordance guidelines standard prevailing, but the fact remains found damage to products. The purpose of research to know processing the cashew nut, supervise the quality uses statistics method and total cost for quality control steady. Based on the research done, there are 11 stages production processed of cashew nut. Quality control analysis include: quality control the beginning until the end of the production process, quality control using controlled map analysis these show that the process is controllable, and quality control using cause and effect diagram analysis that show the source of the product’s damage is affected by raw material, human resources, and mechanism. Based on the analysis on total quality cost, actual quality cost the spend by the company are Rp 214.583.333,00 with the total of damage around 8.460 kilograms, and total quality cost over optimum quality are Rp 190.673.096,00 with the total of optimum damage around 5.153,33 kilograms, with the difference of streamlined cost are Rp 23.910.237,00 and the extent of damage differences over the cashew nut products are 3.306,67 kilograms. The recommended suggestion is the company better use statistic quality control method and increase the procedure also the appropriate working method.